2018
DOI: 10.3389/fpsyg.2018.00311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Single Compared to Dual Task Practice on Learning a Dynamic Balance Task in Young Adults

Abstract: Background: In everyday life, people engage in situations involving the concurrent processing of motor (balance) and cognitive tasks (i.e., “dual task situations”) that result in performance declines in at least one of the given tasks. The concurrent practice of both the motor and cognitive task may counteract these performance decrements. The purpose of this study was to examine the effects of single task (ST) compared to dual task (DT) practice on learning a dynamic balance task.Methods: Forty-eight young ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 29 publications
1
25
0
2
Order By: Relevance
“…Further, both DT practice groups' did not differ in the cognitive task but performed better than the ST motor group in a DT test situation. Thus, we replicated the results of our previous study (Kiss et al, 2018), which showed that DT but not ST practice resulted in motor and cognitive task improvements when tested under DT condition. Based on these findings, it is suggested that DT practice effectively modulates both domains (i.e., motor and cognitive), whereas ST practice is effective to modulate the trained domain (i.e., motor or cognitive) only.…”
Section: Effects Of Dual Compared To Single-task Practicesupporting
confidence: 89%
“…Further, both DT practice groups' did not differ in the cognitive task but performed better than the ST motor group in a DT test situation. Thus, we replicated the results of our previous study (Kiss et al, 2018), which showed that DT but not ST practice resulted in motor and cognitive task improvements when tested under DT condition. Based on these findings, it is suggested that DT practice effectively modulates both domains (i.e., motor and cognitive), whereas ST practice is effective to modulate the trained domain (i.e., motor or cognitive) only.…”
Section: Effects Of Dual Compared To Single-task Practicesupporting
confidence: 89%
“…We used a dynamic balancing task to examine patients’ motor learning performance. The stabilometer is widely used to study motor learning ( Wulf et al, 2003 ; Lewthwaite and Wulf, 2010 ; Kiss et al, 2018 ), including PD populations ( Chiviacowsky et al, 2012 ; Sehm et al, 2014 ). The device consists of a 107 × 65 cm wooden platform (stability platform; Lafayette Instrument Europe; Loughborough, United Kingdom), which is mounted on a fulcrum and has a maximum deviation of 15° to either side.…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics may be especially informative for the design of future dual-task training interventions, where repeated practice with CD/PD interactions may help to expand an individual’s central processing resources for combined cognitive and motor performance. Indeed, previous work has shown that three days of dual-task training (quiet standing while counting backwards by 3 s) improved both cognitive and motor task performance among healthy young adults (Kiss et al., 2018). Thus, practice may enhance central processing resources sufficiently to prevent their being overtaxed in these dual-task circumstances.…”
Section: Discussionmentioning
confidence: 98%